THE INFLUENCE OF DISCOUNT VOUCHERS, ONLINE CUSTOMER REVIEWS, AND PROMOTIONAL COSTS ON THE NET PROFIT OF SHOPEEFOOD MERCHANTS - Eunike Marvella; J.E. Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The aim of this study is to assess how discount vouchers, online customer reviews, and promotional expenses affect the net profit of Shopeefood merchants. The research methodology employed is quantitative, involving a sample size of 120 respondents. Data analysis was conducted using SPSS software. The findings indicate that discount vouchers (X1) significantly affect the net profit of Shopeefood merchants, whereas online customer reviews (X2) and promotional costs (X3) have an impact but are not statistically significant regarding the net profit of Shopeefood merchants (Y). However, simultaneously, all three independent variables do influence the dependent variable.